Transforming Nigeria’s cassava seed entrepreneur policy guidelines for inclusivity and gender responsiveness - Nwanze, O.; Adeleke, O.; Alabi, A.; Bello, A.; Madu, T.; Onyeka, J.; Okoye, B.; Egesi, C.; Osundiya, O.; Liani, M.L.; Cole, S.; Teeken, B. (International Institute of Tropical Agriculture, 2025)
Seed policies and guidelines aim to boost crop productivity and provide a framework for dissemination of certified quality seeds, in line with the objectives of national food security and broader agricultural development goals. Case studies in Oyo, Abia, and Benue states in Nigeria examining gender-based constraints affecting farmer participation as cassava seed entrepreneurs (CSEs) found women, the youth, and migrant farmers to have limited awareness on CSE certification criteria and to face restricted access to resources like land, credit, and finance. An added complication was the requirement of male family members to stand as guarantors for credit for these groups. Cultural barriers such as biased inheritance norms and mobility restrictions were challenges to women’s participation as CSEs. Migrants or non-indigene populations faced biases in land allocation, with their land portions being in distant, insecure land, impacting their participation as CSEs and compliance with National Agricultural Seed Council (NASC) standards and reinforcing existing inequalities. Inclusive strategies such as involvement in cooperative associations to meet land requirements and create finance opportunities, plus fostering community support can enhance participation and create a more diverse, gender-responsive and resilient seed entrepreneurship ecosystem.